Effect of intermittent shade on nitrogen dynamics assessed by 15N trace isotopes, enzymatic activity and yield of Brassica napus L. - Javed, Hafiz Hassan; Hu, Yue; Asghar, Muhammad Ahsan; Brestic, Marian; Abbasi, Majid Ali; Saleem, Muhammad Hamzah; Peng, Xiao; Ghafoor, Abu Zar; Ye, Wen; Zhou, Jing; Guo, Xiang; Wu, Yong-Cheng (Frontiers in Plant Science, 2022)
Modern era of agriculture is concerned with the environmental influence on crop growth and development. Shading is one of the crucial factors that affects the crop growth extensively which is neglected over the years. Therefore, a two-year field experiment was aimed to investigate the effects of shading at flowering (S1) and pod development (S2) stages on nitrogen (N) dynamics, carbohydrates and yield of rapeseed. Two rapeseed genotypes (Chuannong and Zhongyouza) were selected to evaluate the effects of shading on 15N trace isotopes, enzymatic activities, dry matter, nitrogen and carbohydrate distribution and their relationship with yield. The results demonstrated that both shading treatments disturbed the nitrogen accumulation and transportation at maturity stage. It was found that shading induced the downregulation of the N mobilizing enzymes (NR, NiR, GS, and GOGAT) in leaves and pods at both developmental stages. Shading at both growth stages resulted in reduced dry matter of both varieties but only S2 exhibited the decline in pod shell and seeds dry weight in both years. Beside this, carbohydrates distribution toward economic organs was declined by S2 treatment and its substantial impact was also experienced in seed weight and seeds number per pod which ultimately decreased the yield in both genotypes. We also revealed that yield is positively correlated with dry matter, nitrogen content and carbohydrates transportation. Overall, it was noticed that shading at pod developmental stage considerable affected the transportation of N and carbohydrates which led to reduced rapeseed yield as compared to shading at flowering stage. In contrast to Chuannong, the Zhongyouza genotype performed relatively better under shade stress.